Anti-perovskite carbides and nitrides A3BX: A new family of damage tolerant ceramics. (1st March 2020) - Zhang, Wei; Liu, Yuchen; Zhou, Yanchun; Ching, Wai-Yim; Li, Qian; Li, Wenxian; Yang, Jiong; Liu, Bin
Abstract: Synergy effect of high stiffness and good damage tolerance is always the focus of the development of novel structural materials. Herein, a new strategy on the future damage tolerant material design is proposed to merge the strong covalent bonds into the easy shear deformed A 3 B metallic box. This goal is realized by studying 126 A3 BX phases and establishing a database on their mechanical properties through high-throughput first principles calculations. The combination strategies of A 3 B metallic box and XA 3 octahedra show intensive influences on the expected mechanical properties. The family includes 49 quasi-ductile compounds. Among them, four compounds (Ti3 AlN, Mn3 CuN, Ti3 TlN and Ni3 SnN) exhibit excellent damage tolerance and the other six compounds (Mn3 NiN, Mn3 GaC, Mn3 GaN, Mn3 SnC, Cr3 SnN, Co3 AlC) show both damage tolerance and high stiffness. Their competitive high temperature properties are demonstrated through the detailed investigation on the typical cases of Co3 AlC and Ti3 TlN. This study leads a novel direction for the design of the future quasi-ductile and high stiffness ceramics.